EVALUATION OF THE EFFECTIVENESS OF USING HYDROPONIC GREEN FODDER IN THE DIET OF LABORATORY MICE - T. Afanasev; A. Kashaeva; E. Kirillov; I. Koval (Animal Health and Biosafety, 2026)
The article presents a technology for producing hydroponic green fodder (HGF) from awned barley grain, including cleaning, ultraviolet disinfection, and germination in automated multi-tier trays at a temperature of 22-24 °C, illumination of 600 lx, and a 12-hour photoperiod for 7 days. The effect of different HGF inclusion rates (5, 10, and 15% on a dry matter basis) on survival, live body weight dynamics, and linear growth parameters of laboratory mice was studied during a 30-day experiment. It was established that feeding HGF at 15% of dietary dry matter increased average daily gains by 48.5% (p < 0.01), improved survival to 100% (compared with 80% in the control group, p < 0.05), and positively affected exterior parameters: body length increased by 8.8% (p < 0.01), while tail length increased by 15.1% (p < 0.01). A direct dose-dependent relationship was identified: an increase in the proportion of HGF in the diet was accompanied by a proportional improvement in all studied parameters. The physiological condition of the experimental groups was characterized by high activity, a glossy hair coat, and the absence of gastrointestinal disorders, indicating normalization of metabolic processes. The results are consistent with studies by other authors investigating the effectiveness of HGF in various animal species. Hydroponic green fodder is recommended for use as a biologically active feed supplement in the diets of laboratory animals under vivarium conditions, particularly during the winter-spring period, to compensate for the lack of fresh green feed, increase productivity, and improve physiological status. An inclusion rate of 15% on a dry matter basis was considered optimal, providing the maximum beneficial effect without adverse effects.